2009
DOI: 10.1186/1423-0127-16-114
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Ca2+ transport across sarcolemma but enhanced spontaneous activity in cardiomyocytes isolated from left atrium-pulmonary veins tissue of myopathic hamster

Abstract: BackgroundSeveral lines of evidence point to a particularly important role of the left atrium (LA) in initiating and maintaining atrial fibrillation (AF). This role may be related to the location of pulmonary veins (PVs) in the LA. The aim of the present study was to investigate the action potential (AP) and ionic currents in LA-PV cardiomyocytes isolated from Bio14.6 myopathic Syrian hamsters (36-57 week-old) versus age-matched F1B healthy control hamsters.Methods and ResultsWhole-cell patch-clamp techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Increasing intra-atrial pressure, as found in heart failure, accelerates pulmonary vein firing in intact sheep hearts (Kalifa et al, 2003 ). While this increase appears to be mediated by changes in calcium cycling leading to more delayed afterdepolarizations (Chang et al, 2008 ; Loh et al, 2009 ; Lin et al, 2016 ), the cellular changes responsible for this are unclear. While increased levels of circulating B-type natriuretic peptide have been suggested to increase the rate of spontaneous firing due to increased I Ca(L) and I NCX but decreased late I Na (Lin et al, 2016 ), others report an increase in DADs in the setting of heart failure with decreased I Ca(L) and increased late I Na (Chang et al, 2008 ).…”
Section: The Interplay Between Heart Failure and Atrial Fibrillationmentioning
confidence: 99%
“…Increasing intra-atrial pressure, as found in heart failure, accelerates pulmonary vein firing in intact sheep hearts (Kalifa et al, 2003 ). While this increase appears to be mediated by changes in calcium cycling leading to more delayed afterdepolarizations (Chang et al, 2008 ; Loh et al, 2009 ; Lin et al, 2016 ), the cellular changes responsible for this are unclear. While increased levels of circulating B-type natriuretic peptide have been suggested to increase the rate of spontaneous firing due to increased I Ca(L) and I NCX but decreased late I Na (Lin et al, 2016 ), others report an increase in DADs in the setting of heart failure with decreased I Ca(L) and increased late I Na (Chang et al, 2008 ).…”
Section: The Interplay Between Heart Failure and Atrial Fibrillationmentioning
confidence: 99%